2016
DOI: 10.3354/meps11641
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of marinas as nursery grounds by rocky fishes: insights from four Diplodus species in the Mediterranean

Abstract: The construction of marinas along the shoreline has caused substantial habitat destruction within the sheltered coastal areas previously used as nursery grounds by many fish species. However, although the negative ecological impacts of these constructions have been reported extensively, their potential roles in the functioning of the coastal zone remain largely unknown. Here, we surveyed the juveniles of 4 Diplodus species in 5 marinas located along the French Mediterranean coast to assess whether rocky fishes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 67 publications
(106 reference statements)
1
39
0
Order By: Relevance
“…As described in other studies (BOUCHOUCHA et al, 2016;MERCARDER et al, 2017), the micro-habitats complexification of the port infrastructures was associated with positive effects both on species richness and densities of juvenile stages of fish in comparison to non-equipped port infrastructures studied as control sites (LAPINSKI et al, 2015).…”
Section: Urchins Module Used On Riprap Dikesmentioning
confidence: 61%
See 3 more Smart Citations
“…As described in other studies (BOUCHOUCHA et al, 2016;MERCARDER et al, 2017), the micro-habitats complexification of the port infrastructures was associated with positive effects both on species richness and densities of juvenile stages of fish in comparison to non-equipped port infrastructures studied as control sites (LAPINSKI et al, 2015).…”
Section: Urchins Module Used On Riprap Dikesmentioning
confidence: 61%
“…As in other studies (e.g. BOUCHOUCHA et al, 2016), initial monitoring conducted on the inner sides of this port have highlighted that juvenile stages of fish can be observed along pile wharfs and riprap dikes. However, diving observations also concluded that many ecological factors described in suitable Mediterranean nurseries…”
Section: Technical and Ecological Contextmentioning
confidence: 71%
See 2 more Smart Citations
“…A large number of studies have focused on the role of artificial structures such as fish attracting devices (Carr andHixon 1997, Rilov andBenayahu 2000) and their contribution to increasing fish biomass (Bohnsack 1989). Though marinas are among the most widespread artificial structures along the shoreline of the world, studies focusing on fish assemblages associated with marinas are still scarce (Clynick 2006, 2008, Bouchoucha et al 2016). Breakwaters at the outer sides of marinas are frequently colonized by a range of fishes, at both juvenile and adult stages (Pizzolon et al 2008, Cenci et al 2011, Pastor et al 2013.…”
Section: Introductionmentioning
confidence: 99%